Research on High-Quality Urbanization Development and Optimization Pathways Based on the Coupling Coordination Perspective of “Population–Land–Economy–Environment”: A Case Study of Jiangsu Province, China - Siyuan Huang; Yaoben Lin (Land)
Urbanization is a key driver of economic and social development. But balancing economic growth with ecological protection remains a global challenge. This paper examines urbanization in Jiangsu Province, China, analyzing data from its 13 prefecture-level cities between 2008 and 2022, with a focus on the population, land, economy, and ecological dimensions. Using a coupling coordination model, we analyze the temporal and spatial evolution, coupling relationships, and optimization of urbanization in the province. The key findings of this study are as follows: (1) Population urbanization increased from 54.3% in 2008 to 74.42% in 2022, with significant regional disparities. (2) Land urbanization expanded, with built-up areas growing from 2905 km2 to 4920 km2, although the northern region still shows potential for further development. (3) Economic urbanization grew, with secondary and tertiary industries contributing 96% to GDP by 2022, highlighting regional economic disparities. (4) Environmental urbanization improved, with reductions in industrial emissions and 100% harmless treatment of municipal waste. (5) The degree of coupling coordination rose from 0.513 to 0.851, reflecting improved alignment across the four urbanization dimensions. However, disparities persist across cities, requiring tailored urbanization policies to enhance quality of life, land management, economic development, and ecological governance, thus promoting high-quality urbanization.